The Comparison of Pierre Robin Sequence and Non-Syndromic Cleft Palate - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Introduction: The aim of this study was to evaluate pre-operative nutritional status, associated syndromes and abnormalities, and post-operative outcomes of patients with Pierre Robin Sequence (PRS) versus those with non-syndromic isolated cleft palate (CIP). Methods: Between January 1995 and December 2013, patients with a cleft palate Veau I-II according to the Veau classification with and without PRS who underwent primary repair were retrospectively analyzed. The nutrition status, age at the time of palatoplasty, additional anomalies, gestational complications, and postoperative speech abnormalities and outcomes were evaluated. Results: A total of 59 patients with PRS (PRS group) and 132 patients without PRS (non-PRS group) were included in the study. Of all patients, 92 were males and 99 were females with a mean age of 14 +/- 4.18 (range, 6 to 26) years. The rate of gestational complications, enteral nutrition, complete cleft, additional anomalies, and velopharyngeal insufficiency was significantly higher in the PRS group (P < 0.05). However, the incidence of fistulas and age at the time of palatoplasty did not significantly differ between the groups. Conclusion: Based on our study results, enteral nutrition, respiratory problems, pregnancy complications, velopharyngeal insufficiency, and additional anomalies, but not post-operative palatal fistulas, are more frequently seen in patients with PRS. Although pre-operative care and treatment and rehabilitation in patients with PRS are more complicated than those with the CIP, our experience demonstrates that meticulous repair and follow-up can minimize complications, such as fistulas.
Keywords: Cleft lip palate; cleft palate; pierre robin sequence; VELOPHARYNGEAL INSUFFICIENCY; INSTITUTIONAL EXPERIENCE; OTITIS-MEDIA; CHILDREN; MANAGEMENT; OUTCOMES; GROWTH; AIRWAY; FISTULAS; INFANTS